DAPATKAH TEORI FRAUD TRIANGLE MENJELASKAN KECURANGAN DALAM LAPORAN KEUANGAN? - Ratmono, Dwi; Diany, Yuvita Avrie; Purwanto, Agus (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2017)
The objective of this study is to test the ability of fraud triangle theory to explain financial statement fraud phenomena. To achieve the objective, this research examines factors which affect financial statement fraud. Based on fraud triangle theory, there are three variables hypothesized affect fraud which are pressure, opportunity and rationalization. This study uses data of 27 companies which did financial statement fraud and 27 other companies as pair matched sample. Data collected from annual report published by website Indonesian Stock Exchange (IDX). Data then analyzed using logistic regression analysis. The result of this study shows significant positive relation between pressure and opportunity with financial statement fraud. Rationalization is not supported as determinant of financial statement fraud. This study provides partial support for fraud triangle theory in explaining financial statement fraud phenomena.